MODEL OF TRANSPORT SUPPORT FORMATION FOR PROJECT-ORIENTED COMPANY - Русанова, Светлана (SWorldJournal, 2021)
The paper deals with a problem related to the transportation of projects, the essence of which is to determine an effective option for a set of projects of a project-oriented company. At the same time, by an effective option we mean an option that meets t